2020
DOI: 10.1002/aet2.10543
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences Among Milestone Assessments in a National Sample of Pediatric Emergency Medicine Fellowship Programs

Abstract: Background: Understanding gender gaps in trainee evaluations is critical because these may ultimately determine the duration of training. Currently, no studies describe the influence of gender on the evaluation of pediatric emergency medicine (PEM) fellows. Objective:The objective of our study was to compare milestone scores of female versus male PEM fellows. Methods: This is a multicenter retrospective cohort study of a national sample of PEM fellows from July 2014 to June 2018. Accreditation Council for Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Of the seven included studies that reported quantitative results across a wide range of different assessment types, 12,32,34–37 six did not identify any differences in scores between female and male residents 32,34–37 . The study by Dayal et al 12 was the only study to report statistically significant differences attributable to gender.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the seven included studies that reported quantitative results across a wide range of different assessment types, 12,32,34–37 six did not identify any differences in scores between female and male residents 32,34–37 . The study by Dayal et al 12 was the only study to report statistically significant differences attributable to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the 10 studies examined assessments based on the Accreditation Council for Graduate Medical Education (ACGME) EM or PEM milestones. 12,15,32,[35][36][37]39,40 Four studies investigated and reported the impact of assessor gender on resident performance scores, and none of the studies reported a statistically significant difference in scores between female and male assessors. 15,32,34,37 Only three studies included a priori definitions of meaningful differences in outcomes, 32,34,37 two of which included sample size calculations.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations